Influence of Aerosols on Lightning Activities in Java Island, Indonesia - Rizqy Shubri, Ahmad; Vonnisa, Mutya; Marzuki, Marzuki (Trends in Sciences, 2023)
Lightning is one of the natural disasters that cause significant financial losses and even fatalities. Therefore, it is necessary to understand the characteristics of lightning and related factors take appropriate preventive and mitigation measures. This work investigated the influence of aerosols and atmospheric thermodynamic factors on lightning in Java Island using 16 years of data (1998 - 2013) from the Tropical Rainfall Measuring Mission (TRMM) satellite. Aerosol data were obtained from the Modern Era Retrospective Analysis for Research and Applications version 2 (MERRA-2). Furthermore, convective available potential energy (CAPE) and potential temperature data were taken from the fifth-generation ECMWF atmospheric reanalysis (ERA-5) data. The intensity of lightning strikes in the western part of Java, such as Jakarta and Banten, is higher than in the eastern part, corresponding to the distribution pattern of aerosols, especially sulfate aerosols, sea salt aerosols, and black carbon aerosols. Sea salt aerosols have an inverse relationship with lightning, as these coarse-sized aerosols tend to inhibit convection. An increase in CAPE and potential temperature generally leads to higher lightning intensity. However, in cases where CAPE values are extremely high, such as in Jakarta, the intensity of lightning decreases. A similar pattern can be observed with potential temperature. An inverse relationship between lightning and potential temperature is observed in regions at higher elevations. The peak time for CAPE and potential temperature coincide with the peak intensity of lightning, which typically occurs during the rainy season, while the peak of AOD occurs earlier, during the pre-monsoon (September-October-November). The highest values of sea salt AOD are observed during the dry season (June-July-August) when lightning is minimal. These variations in peak times are particularly evident in the western regions of Java, where AOD values are high. The findings of this study can aid in lightning disaster mitigation efforts on Java Island. HIGHLIGHTS The intensity of lightning strikes in the western part of Java is higher than in the eastern part Sea salt aerosols have an inverse relationship with lightning, as these coarse-sized aerosols tend to inhibit convection An increase in CAPE and potential temperature generally leads to higher lightning intensity The peak time for CAPE and potential temperature coincide with the peak intensity of lightning The highest values of sea salt AOD are observed during the dry season when lightning is minimal GRAPHICAL ABSTRACT